The effect of grammar translation method and text-based instruction on students' vocabulary knowledge - Salma Ratna Dianti; Hamdan Hidayat; Muhammad Andriana Gaffar (Universitas Papua, 2026)
Although vocabulary instruction has been continuously integrated into EFL classrooms, the findings suggest that students possess variable degrees of vocabulary knowledge, depending on the teaching technique employed. This study was conducted to examine the impact of the Grammar Translation Method (GTM) and Text-Based Instruction (TBI) on students' vocabulary knowledge and to compare the learning outcomes of the two methodologies. A quantitative non-experimental research design was used, with 59 tenth-grade students from SMAN 25 Bandung. Participants were separated into two groups: 30 got GTM-based training (K1) and 29 were taught with TBI (K2). The Vocabulary Size Test (VST) scores were examined using descriptive statistics with normality tests and the Mann-Whitney U test. The study found a notable disparity in vocabulary knowledge between the two groups (Sig. 0.001 < 0.05), with the GTM group having a higher average ranking (37.40) than the TBI group (22.34). While GTM was more effective at vocabulary retention and organization, TBI promoted contextualized vocabulary learning and critical thinking. These findings suggest that both strategies have distinct benefits depending on instructional aims, and that combining them may promote more complete vocabulary development in EFL environments. Future studies should investigate hybrid techniques across various learning settings.